Social Entrepreneurship and the Role of Universities - A rationale for guiding social entrepreneur coaching along the social business development process - Oliveira, Manuel Au-Yong (2009)
Taking advantage of entrepreneurial talent seems to be of paramount importance for economic development and all over the world plans have been designed to achieve this endeavour. Research involving students at various levels of education and in various courses has been performed by academics worldwide. Empirical studies however have been mostly concentrated on undergraduate students' intents. Postgraduate student analyses are rare but needed given the widespread fears of unemployment and increasing dissatisfaction with employment at this level. Social entrepreneurship in particular is an area of inquiry which is still in its infancy. Based upon Weerawardena and Mort's (2006) multidimensional model of social entrepreneurship: SVC = f (I, P, RM) subject to S, SM, EWhere SVC: social value creation; I: innovativeness; P: proactiveness; RM: risk management; S: Sustainability; SM - social mission; E: environmentWe provide a rationale for guiding social entrepreneur coaching along the social business development process at the postgraduate level.